Physical Stability of Hair Tonic Contain Ethanol Extract Galangal (Alpinia galanga L.) Rhizome and Aloe Vera Leaf Filtrate (Aloe vera L.) - Akib, Nur illiyin; Tendri Adjeng, Andi Nafisah; Lakasa, Rahiswari Pramudita; Suryani, Suryani; Sartinah, Ari; Ritonga, Halimahtussaddiyah; Armadany, Fery Indradewi (Fakultas Farmasi Universitas Halu Oleo, 2020)
AbstractFormulation and stability testing of hair tonic contain galangal rhizome (Alpinia galanga L.) ethanol extract and Aloe vera L. filtrate has been done as alternative for dandruff removal and hair growth. This study aimed to produce stable hair tonic. Galangal rhizome extract obtained by maceration method using ethanol and aloe leaf filtrate obtained by filtering. Extracts and filtrates characterized include water and ethanol soluble content, water and ash content. Hair tonic was formulated by mechanical mixing method with variations of galangal rhizome ethanol extract and aloe vera leaf filtrate which were 4% and 12.5%; 5% and 25%; 6% and 37.5%. Hair tonic prepared were tested for stability by cycling test method including organoleptic, homogeneity, pH, and viscosity. The characteristics of the galangal rhizome ethanol extract were 12% water soluble extract, 12% ethanol soluble extract, 3% water content, and 2% ash content. The characteristics of Aloe vera leaf filtrate were 10% ethanol soluble extract, 1.6% water soluble extract, and 1% ash content. Stability testing shows that hair tonic preparations are organoleptically stable and homogeneous. The pH values before and after cycling test for formulas A, B, and C were 5.27 to 5.34, respectively; 5.00 to 5.15; and 4.87 to 5.05. Viscosity before and after the cycling test for formulas A, B, and C were 1.178 to 1.676 cPs respectively; 1,306 to 1,883 cPs; and 2,148 to 2,296 cPs. It is concluded that hair tonic prepared are stable based on the requirements of Indonesian National Standard (SNI).